2011
DOI: 10.1186/1479-5876-9-55
|View full text |Cite
|
Sign up to set email alerts
|

Safety and pharmacokinetics of recombinant human hepatocyte growth factor (rh-HGF) in patients with fulminant hepatitis: a phase I/II clinical trial, following preclinical studies to ensure safety

Abstract: BackgroundHepatocyte growth factor (HGF) stimulates hepatocyte proliferation, and also acts as an anti-apoptotic factor. Therefore, HGF is a potential therapeutic agent for treatment of fatal liver diseases. We performed a translational medicine protocol with recombinant human HGF (rh-HGF), including a phase I/II study of patients with fulminant hepatitis (FH) or late-onset hepatic failure (LOHF), in order to examine the safety, pharmacokinetics, and clinical efficacy of this molecule.MethodsPotential adverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 39 publications
0
39
0
1
Order By: Relevance
“…12 Recent phase I/II clinical studies in patients with some of those organ failures revealed no severe side effects of HGF treatment in humans. 13,14 However, the multiple biological activities of HGF do raise the possibility that undesirable effects might occur after systemic administration without careful control of the dose regimen. Therefore, it is essential to understand the overall pharmacokinetics of HGF in humans.…”
Section: Introductionmentioning
confidence: 99%
“…12 Recent phase I/II clinical studies in patients with some of those organ failures revealed no severe side effects of HGF treatment in humans. 13,14 However, the multiple biological activities of HGF do raise the possibility that undesirable effects might occur after systemic administration without careful control of the dose regimen. Therefore, it is essential to understand the overall pharmacokinetics of HGF in humans.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, phase I clinical studies by intravenous administration of recombinant HGF have begun, and a critical toxic effect has not been noted in these studies [10]. We have previously indicated that the basic pharmacokinetic profiles and parameters obtained from experimental animal species (mouse, rat and monkey) could be extrapolated to those in humans [29].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the potential tissues for clinical development of HGF include the kidney and liver. Phase I clinical trials of recombinant human HGF have been conducted in patients with fulminant hepatitis [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Transient MKK4 inhibition therefore has potential in the therapy of acute liver failure. This would require fast-acting MKK4 blockage to facilitate restoration of a critical hepatocyte mass before aggravation of the illness to multi-organ failure (Ido et al, 2011). For this, antisense oligonucleotides could be used that reach hepatocytes and knock down targeted genes within hours after intravenous injection (Ng et al, 2012).…”
mentioning
confidence: 99%